Source-Based L1 Student Writing Development: Analyzing the Relationships Among Functional Dimensions of Source Use and the Quality of Source Use. (April 2023) - Doolan, Stephen M.
Source-based writing is a complex and frequently occurring task type in postsecondary education. While a large body of research now exists investigating source-based student writing, few studies have used corpus-based methods to investigate L1 student performance on source-based writing tasks and to connect this performance to the holistic quality of source use. The current study investigates the relationship among functional dimensions of source use, operationalized for each text ( N  = 150) as factor scores from a previously conducted multidimensional analysis, and the quality of source use through a simultaneous multiple regression. Then, using the two functional dimensions that emerged as significant predictors of the holistic quality of source use, a qualitative analysis was conducted to investigate how the most strongly loading variables on those two functional dimensions may be contributing to the effectiveness of source use. Implications are discussed as they relate to the development of source-based L1 student writing.